Menavigasi Jalan Menuju Perubahan: Mengkaji Faktor Rasional, Politik, dan Kultural dalam Konteks Instansi Pemerintah - Reskino, Reskino; Afrizon, Afrizon (JMB : Jurnal Manajemen dan Bisnis, 2024)
This research aims to examine the influence of rational, political and cultural factors on the adoption and implementation of performance information in the context of government organizations. This research involved 85 respondents who participated in a questionnaire survey to collect relevant data. Data analysis was carried out using the multiple regression method. The research results show that in terms of the adoption of performance information, the internal group has a significant influence, while other groups do not have a significant influence. However, when we talk about the implementation of performance information, the role of internal groups and external groups both have a significant influence. This research also reveals that rational, political and cultural factors are able to explain as much as 35% of the variation in the adoption of performance information and as much as 57% of the variation in its implementation. The findings of this research provide valuable insight into the factors that influence the adoption and implementation of performance information in government organizations, as well as the extent to which these factors can explain variation in the adoption and implementation process. The implications of these findings can help government organizations to increase their efforts to adopt and implement performance information more effectively